CD40L coding oncolytic adenovirus allows long-term survival of humanized mice receiving dendritic cell therapy. (3rd October 2018) - Zafar, Sadia; Sorsa, Suvi; Siurala, Mikko; Hemminki, Otto; Havunen, Riikka; Cervera-Carrascon, Victor; Santos, João Manuel; Wang, Hongjie; Lieber, Andre; De Gruijl, Tanja; Kanerva, Anna; Hemminki, Akseli
ABSTRACT: Dendritic cells (DCs) are crucial players in promoting immune responses. Logically, adoptive DC therapy is a promising approach in cancer immunotherapy. One of the major obstacles in cancer immunotherapy in general is the immunosuppressive tumor microenvironment, which hampers the maturation and activation of DCs. Therefore, human clinical outcomes with DC therapy alone have been disappointing. In this study, we use fully serotype 3 oncolytic adenovirus Ad3-hTERT-CMV-hCD40L, expressing human CD40L, to modulate the tumor microenvironment with subsequently improved function of DCs. We evaluated the synergistic effects of Ad3-hTERT-CMV-hCD40L and DCs in the presence of human peripheral blood mononuclear cells ex vivo and in vivo . Tumors treated with Ad3-hTERT-CMV-hCD40L and DCs featured greater antitumor effect compared with unarmed virus or either treatment alone. 100% of humanized mice survived to the end of the experiment, while mice in all other groups died by day 88. Moreover, adenovirally-delivered CD40L induced activation of DCs, leading to induction of Th1 immune responses. These results support clinical trials with Ad3-hTERT-CMV-hCD40L in patients receiving DC therapy.